Electrocardiographic changes in normal and abnormal canine pregnancy - Blanco, Paula Graciela (2012)
The aim of this study was to describe the canine electrocardiographic changes in the course of normal and abnormal pregnancy. Twenty-three Brucellosis-negative pregnant bitches were retrospectively classified as normal (n=12) or abnormal (n=11). A control group of non-pregnant dioestrous bitches (n=10) was also included. Normal pregnant females delivered healthy puppies at term while abnormal animals interrupted their pregnancy between days 52-60 (from estimated luteinizing hormone peak) or presented perinatal litter death higher than 60%. All the bitches were electrocardiographically evaluated every 10days from day 0 to day 65 of the oestrous cycle, to parturition or abortion. Percentage heart rate change increased 31.3% from day 40 to 60 in normal gestation while it decreased -1.8% in dioestrous bitches, although it did not change in the abnormal group (p<0.01). In the abnormal pregnant group but not in the others, percentage QRSa change fell to -34% on day 60 (p<0.01). At the same time point, percentage QRSd change was 6.2% vs -4.9% in normal gestations and dioestrous animals, respectively (p<0.05). Corrected QT interval augmented from day 40 onwards up to 9.9% and 4.3% in the normal pregnant and dioestrous groups, respectively, while it remained unchanged in abnormal gestations (p<0.05). It is concluded that during normal canine pregnancy, some electrocardiographic parameters begin changing from day 40 onwards, and that pathological gestations differ from normality from day 30. The use of electrocardiography in canine obstetrics might contribute to identify abnormal outcomes before they become clinically evident.